A study on factor of stress towards productivity of oil palm workers at Felda Techno-Plant, Gugusan Waha, Kota Tinggi / Muhd Faiz Mohamad - Mohamad, Muhd Faiz (Faculty of Plantation and Agrotechnology, 2019)
Oil palm is a major crop in Malaysia that contribute to economic stabilization. The output of oil palm depends on harvester productivity. Sometimes the productivity can be disturbed by some factor like stress. Stress is invisible thing that can give harvester sick and harm that they should avoid. The survey was conducted to recognize the relationship of stress with oil palm workers’ productivity, which are consist the factor of wages, workload, management style and the last factor is social influence pressure. The major aim of the survey is to determine the relationship between the factors of stress that affects the productivity of oil palm workers, to evaluate the dominant factor of stress that influences the productivity of oil palm workers and to make appropriate recommendations to manage the stress problem based on the finding of the study. The study was focused on oil palm harvester that working in Felda techno-plant In Johor district and 80 respondents were identified to be asked by using a questionnaire and interview section. This study was carried out using a questionnaire distributed to the respondents and the result analyzed by using Statistical Package for Social Science (SPSS). Nevertheless, the results show one of the three factors of stress is not correlate which is workloads, where it not have any relationship with oil palm workers’ productivity. The result in multiple linear regression which is the most dominant factor is wages of oil palm workers and following factor that contribute to stress is the social influence pressure and management style. The total correlated from factors that influence the oil palm workers’ productivity was 0.195. It can explain that the independent variable are 19.5 %, affecting the oil palm workers’ productivity.